Pola Interaksi Sosial Warga Binaan pada Rumah Tahanan Provinsi Banten : (Studi Lembaga Pemasyarakatan Rutan Provinsi Banten) - Muhammad Nuruddin Arief; Haryono Haryono; Stefany Afrizal (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This research is motivated by the importance of understanding the dynamics of social interaction of prisoners in the Class II B Detention Center of Serang City, Banten Province. The focus of the research is the pattern of relationships between prisoners as well as interactions between prisoners and detention officers that affect social life in the environment. The purpose of this study is to identify the associative and dissociative processes that occur among prisoners and explore the factors that influence the pattern of social interaction in detention centers. The research methodology used is a descriptive qualitative approach, with data collection techniques through direct observation, in-depth interviews, and document analysis. This approach allows in-depth exploration of complex social dynamics in closed environments such as prisons. The results show that social interactions between prisoners include associative processes, such as cooperation in daily activities, and dissociative processes, such as competition and conflict triggered by limited resources and social hierarchy. In addition, interactions between prisoners and officers often vary, ranging from formal relationships in coaching activities to informal relationships that are emotional in nature. The conclusion of this study emphasizes that the pattern of social interaction in detention centers is strongly influenced by the social background of prisoners, family support, and the existing hierarchical structure. This research provides recommendations for the management of detention centers that are more inclusive and support the rehabilitation process of prisoners.